Political leaders and young people: interaction in social networks - A. A. Komarova (Цифровая социология, 2021)
In modern Russian society, there is a deep gap between political activity and active political communication with young people, bringing information to this target audience. Political leaders are the force that is able to convey to people values and guidelines, the meaning of life, to show the way to the future, to lead for the implementation of the necessary changes in the social, political, and economic life of society. However, the established methods of communication are not effective, as a generation has grown up with different social ideas about political leaders and other communication needs. This article is devoted to the study of the interaction of political leaders with young people through the mass media at the current stage of development of Russian society. The paper considers the theoretical foundations of the research of the youth audience. As a result of a comprehensive study, the author revealed the awareness of young people about current politicians. The article takes as a basis the names of politicians from the top 100 most influential politicians in Russia, according to the Agency for Political and Economic Communications. The first part of the research is devoted to the study of the value orientations of modern youth. The paper reveals the problems in communication between modern politicians and young people, investigates the information channels used by young people to receive current political news. The most important source of political information for the youth audience is the Internet and social networks. This is due to the increasing role of social networks in the global communication processes in general, as well as the involvement of the youth audience in the media consumption of social network content. Young people see the greatest communication problems in the status and financial gap between current politicians and youth groups, as well as the difference in value orientations and the age barrier. For a comparative analysis of the data, the sample was divided according to the criteria of age (respondents were divided into three age groups) and gender.